Diagnostic accuracy of 18F Prostate Specific Membrane Antigen (PSMA) PET-CT radiotracers in staging and restaging of high-risk prostate cancer patients and patients with biochemical recurrence: protocol for an overview of reviews [version 2; peer review: 2 approved] - Susan Ahern; Kieran A. Walsh; Lydia O'Sullivan; Andrew Dullea; Máirín Ryan; Kirsty O'Brien; Patricia Harrington; Susan M. Smith; Marie Carrigan; Maeve McGarry (HRB Open Research)
Background Correct staging and risk stratification is essential in ensuring prostate cancer patients are offered the most appropriate treatment. Interest has been growing in the use of radiotracers targeting prostate specific membrane antigen (PSMA), including the use of 18F-PSMA PET-CT, as part of the primary staging or restaging of prostate cancer. Preliminary scoping identified a number of relevant systematic reviews and meta-analyses; however, individually, these each appear to look at only part of the picture. An overview of reviews aims to systematically identify, appraise and synthesise multiple systematic reviews, related to a relevant research question or questions. We present a protocol for an overview of reviews, which aims to collate existing evidence syntheses exploring the diagnostic accuracy of 18F-PSMA in staging and restaging of prostate cancer. It also aims to highlight evidence gaps in prostate cancer staging or restaging. Methods This protocol is reported in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for systematic review protocols (PRISMA-P). The search strategy will be designed in consultation with a librarian. Searches will be performed in Medline (EBSCO), Embase (Ovid), Google Scholar and the Cochrane Database for Systematic Reviews, supplemented by a targeted grey literature search, forward citation searching and searching reference lists of included reviews. No language or date restrictions will be applied to the eligibility criteria or the search strategy. Title & abstract and full text screening will be performed independently by two reviewers. Data will be extracted by one reviewer and checked in full by a second reviewer. Quality appraisal will be performed using the Risk of Bias in Systematic Reviews (ROBIS) tool independently by two reviewers, and results will be narratively synthesised. Conclusions This overview of reviews may be of interest to healthcare professionals, academics and health policy decision-makers. Registration OSF (September 7, 2023).